Teachers’ Involvement in Children’s Transition from the Pre-primary to Class 1 in Soy Division, Eldoret West District, Uasin Gishu County - Kisilu , Kitainge; Koskey , Selina J.; Arusey, Koskey J. (African Journal of Education,Science and Technology (AJEST), 2015)
Transitions between Pre-primary and primary school can only be successful if a harmonious relationship exists between the role players influencing the course the child has to navigate. The teachers‘ involvement in children‘s transition from the Pre-primary to class One in Soy Division was the purpose of study. The Bronfenbrenner‘s Ecological Systems theory was used and descriptive survey design adopted. Simple random sampling used to select 14 private and 22 public schools. The respondents were head teachers, Parent Teacher Association chair-persons, class one and pre-primary school teachers from the sampled schools. Questionnaires and interview schedules were used in data collection. Obtained data was analysed using descriptive statistics. The use of play and the display of the children‘s work were the only teaching strategies almost equally used by the teachers in both the Pre-primary and Class One levels. The use of parents as resource persons was below average in the two class levels. The use of thematic teaching approach and the keeping of the children‘s health records were the strategies that were used mostly by the teachers of the Pre-primary school levels. Most of the teachers in the Pre-primary used the thematic teaching approach and also kept their children‘s health records as compared to the Class One teachers. Teachers in the lower primary need refresher courses so that they are able to understand the strategies appropriate for enhancing a smooth transition of children from pre-primary to class One. Ministry of Education in the county Government need to provide funds to schools to enable school administration play its role well.